Optimization design and assessment of the effect of seepage control at reservoir sites under karst conditions: a case study in Anhui Province, China - Zhang, Wenbing; Shen, Zhenzhong; Chen, Guanyun; Zhang, Wanlin; Xu, Liqun; Ren, Jie; Wang, Fei (Hydrogeology journal, 2021)
Seepage analysis and assessment of the effect of seepage control at reservoir sites are essential parts of dam design and operations, and of considerable significance for the safe and economic design of the masses and hydraulic structures associated with reservoir sites. In this study, a systematic process is provided for the optimal design and assessment of seepage control of reservoir dams under karst development conditions. A reservoir dam planned for construction in the middle-upper reaches of the Huayang River in China is selected as a case example for illustration. A three-dimensional equivalent continuum seepage finite-element numerical model is applied to investigate the effectiveness of the proposed and optimized seepage-control schemes, and it is calibrated by an inversion analysis of the initial seepage field based on the flexible tolerance method and field penetration test data. By analyzing the sensitivity of seepage discharge to the length and depth of the grouting curtain, a safe and economic seepage-control optimization scheme is suggested. Additionally, the sensitivity of seepage discharge to the hydraulic conductivity of the limestone layer is analyzed, and the results show that the hydraulic conductivity of the limestone layer has a significant impact on the seepage discharge of the reservoir site. The methodology and results derived from this study can provide technical support and reference for the optimal design and assessment of seepage control for reservoir dam engineering under karst conditions.